Pengembangan E-Modul Pembelajaran Berbasis Web pada Mata Pelajaran Gambar Teknik Listrik di Sekolah Menengah Kejuruan - Arif, Chandra; Ta’ali, Ta’ali; Muskir, Mukhlidi; Refdinal, Refdinal (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this research is to produce a WEB-based learning e-module using Google Classroom that is valid, practical, and effective in Electrical Engineering Drawing subjects. WEB-based learning e-modules using Google Classroom are designed to improve student understanding to improve student learning outcomes. This research method uses Research and Development (R&D) with 4-D development procedures (Define, Design, Develop, Dissemination). The data analysis technique used descriptive analysis techniques to describe the validity, practicality, and effectiveness of WEB-based learning e-modules using Google Classroom. The results obtained from this development research: The validity of the WEB-based learning e-module using Google Classroom is declared valid on the media and material aspects. The practicality of WEB-based learning e-modules using Google Classroom from teacher and student responses is stated to be very practical. The effectiveness of WEB-based learning e-modules using Google Classroom is declared effective in improving learning outcomes. Based on the findings of this study, it was concluded that the WEB-based learning e-module using Google Classroom was declared valid, practical, and effective to be used as a learning aid in Electrical Engineering Drawing subjects.